Acute ischemic stroke associated with nephrotic syndrome: Incidence and significance — Retrospective cohort study - Hirotaka Iwaki; Masaru Kuriyama; Shuichiro Neshige; Shinichi Takeshima; Takahiro Himeno; Kazuhiro Takamatsu; Yutaka Shimoe; Hiromitsu Kobayashi; Masahiro Nomoto; Akio Tanaka (eNeurologicalSci, 2015)
We report 10 cases with arterial ischemic stroke (AIS) with nephrotic syndrome (NS), and clarified its incidence and clinical characteristics. The patients having albumin less than 3.0 g/dl and serum cholesterol greater than 250 mg/dl at the same time were retrospectively screened from 11,161 cases of stroke. Furthermore, the patients of AIS showing heavy proteinuria were selected. The 10 cases were diagnosed as AIS with NS. Its incidence was 0.09% of all kinds of stroke and 0.12% of AIS. Their subtypes were 6 large-artery atherosclerosis, 3 small-vessel occlusion, and 1 cardioembolism. We carried out a retrospective cohort study to assess the association between NS and atherosclerosis progression in AIS patients. Seven AIS patients with NS due to diabetic nephropathy (cases; NS group) were compared with patients with AIS and diabetes mellitus (DM) without NS (control group). Control group subjects were matched in a 2:1 ratio to cases by age, sex, use of medications for DM, and hemoglobin A1c (HbA1c) level. The NS group had high cerebral artery atherosclerosis scores, especially in the anterior circulation. The NS group demonstrated atherosclerosis of the internal carotid and lower extremity arteries, although there were no statistical differences between the two groups. Study subjects had high serum fibrinogen and D-dimer levels, suggesting that AIS patients with NS have a greater degree of hypercoagulability than AIS patients without NS.